Cognitive Impairment in Fibromyalgia: A Meta-Analysis of Case–Control Studies. Issue 5 (June 2018) - Wu, Yu-Lin; Huang, Chun-Jen; Fang, Su-Chen; Ko, Ling-Hsin; Tsai, Pei-Shan
ABSTRACT: Objective: Cognitive dysfunction has been reported in individuals with fibromyalgia. However, findings regarding cognitive function examined using neuropsychological tests have been inconsistent. The aim of the study was to determine domain-specific cognitive impairment in patients with fibromyalgia compared with healthy controls. Methods: We conducted a meta-analysis that systematically searched six databases (PubMed, Ovid MEDLINE, Embase, CINAHL, PsycINFO, and Web of Science) for articles published before September 2017. Results: Twenty-three case–control studies with a total of 2096 participants were included in the meta-analysis. Cognitive function was significantly lower ( g = 0.87, 95% confidence interval [CI] = 0.60–1.15) in individuals with fibromyalgia than in healthy controls. Large effect sizes were found in learning/memory and attention/psychomotor speed ( g = 0.94, p = .013; g = 1.22, p < .001, respectively); medium effect sizes were reported in executive function and working memory ( g = 0.72, p < .001; g = 0.75, p < .001, respectively). Depression and anxiety scores were associated with the effect size of group differences in cognitive function ( B = 0.11, p < .001, 95% CI = 0.09–0.13; B = 0.02, p < .001, 95% CI = 0.01–0.02, respectively). Conclusions: Cognitive impairment across different cognitive domains was found in individuals with fibromyalgia compared with healthy controls. Mood states (depression and anxiety) may explain the heterogeneity across studies.